2020
DOI: 10.48550/arxiv.2006.07054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning the Travelling Salesperson Problem Requires Rethinking Generalization

Chaitanya K. Joshi,
Quentin Cappart,
Louis-Martin Rousseau
et al.

Abstract: End-to-end training of neural network solvers for combinatorial problems such as the Travelling Salesman Problem is intractable and inefficient beyond a few hundreds of nodes. While state-of-the-art Machine Learning approaches perform closely to classical solvers for trivially small sizes, they are unable to generalize the learnt policy to larger instances of practical scales. Towards leveraging transfer learning to solve large-scale TSPs, this paper identifies inductive biases, model architectures and learnin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The authors stated that, based on their findings, NCO methods are not robust enough to handle real world situations beyond what they see in training and do not reliably scale to practical sizes. As we will see in what follows, apart from the generalization issue reported by Joshi et al [24], the application of NCO in COPs poses a number of questions that are worth investigating. For that purpose, in this paper we present a broad analysis addressing those concerns.…”
Section: Related Workmentioning
confidence: 98%
See 2 more Smart Citations
“…The authors stated that, based on their findings, NCO methods are not robust enough to handle real world situations beyond what they see in training and do not reliably scale to practical sizes. As we will see in what follows, apart from the generalization issue reported by Joshi et al [24], the application of NCO in COPs poses a number of questions that are worth investigating. For that purpose, in this paper we present a broad analysis addressing those concerns.…”
Section: Related Workmentioning
confidence: 98%
“…The model infers the matrix in one go and solutions are then obtained by performing a beamsearch over the probability matrix [23]. (2) Autoregressive methods construct the solutions sequentially, adding one item to the solution in each iteration and updating its current state [24].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently several machine learning-based methods such as Joshi et al (2020), Bresson and Laurent (2021), Kool, van Hoof, and Welling (2018) have been developed to address TSP. In these studies, TSP is reformulated as a deep reinforcement learning problem where the actor's policy network is implemented by Graph Neural Network (GNN) or Transformers Vaswani et al (2017) trained using the REINFORCE Williams (1992) method.…”
Section: Related Workmentioning
confidence: 99%
“…For example, a recent study (Tang et al, 2020) has demonstrated the direct benefits of choosing inductive biases that align well with iterative algorithms. Algorithms have also been used to highlight the importance of attention mechanisms (Graves et al, 2014) or to disambiguate various message passing mechanisms for graph neural networks (Richter & Wattenhofer, 2020;Joshi et al, 2020;Veličković et al, 2019).…”
Section: Motivationmentioning
confidence: 99%